2022
DOI: 10.3390/medicina59010008
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis of the Temporomandibular Joint: A Narrative Overview

Abstract: Background and Objectives: This study reviewed the literature to summarize the current and recent knowledge of temporomandibular joint osteoarthritis (TMJOA). Methods: Through a literature review, this work summarizes many concepts related to TMJOA. Results: Although many signaling pathways have been investigated, the etiopathogenesis of TMJOA remains unclear. Some clinical signs are suggestive of TMJOA; however, diagnosis is mainly based on radiological findings. Treatment options include noninvasive, minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 84 publications
(291 reference statements)
2
8
0
Order By: Relevance
“…Moreover, these observational studies primarily employed cross‐sectional designs and did not thoroughly investigate the long‐term effects of early‐life adiposity on the subsequent development of TMDs. Additionally, the criteria for diagnosing TMDs in children under 10 years old are still a subject of debate 30 . By utilizing the MR approach and genetic variants as proxies for each trait, our study consistently demonstrated the effects of early and adult adiposity on TMDs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Moreover, these observational studies primarily employed cross‐sectional designs and did not thoroughly investigate the long‐term effects of early‐life adiposity on the subsequent development of TMDs. Additionally, the criteria for diagnosing TMDs in children under 10 years old are still a subject of debate 30 . By utilizing the MR approach and genetic variants as proxies for each trait, our study consistently demonstrated the effects of early and adult adiposity on TMDs.…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, the criteria for diagnosing TMDs in children under 10 years old are still a subject of debate. 30 By utilizing the MR approach and genetic variants as proxies for each trait, our study consistently demonstrated the effects of early and adult adiposity on TMDs. Our findings suggested that adiposity during specific stages of the life cycle may causally decrease the risk of TMDs.…”
Section: Re Sultssupporting
confidence: 53%
“…The candidate mediators included nine psychology-related traits (depression, feeling lonely, miserable, guilty, fed-up, nervous, worry, hurt, and tense), 19,20 four smoking and dietary behaviours (ever smoked, smoking initial, cigarettes smoked per day, alcohol intake frequency), 21 three adiposity traits (body mass index [BMI], waistto-hip ratio [WHR], body fat percentage), 22 five sleep-related traits (apnea, snoring, insomnia, daytime sleepiness, sleep duration), 23,24 one physical activity (moderate to vigorous physical activity levels), 19 two autoimmune disorders (systemic lupus erythematosus [SLE], Sjogren's syndrome [SS]), 25 insufficient Vitamin D (vitamin D supplement, serum 25-Hydroxyvitamin D levels), 25 estradiol levels in females and males, 26 lower back pain 27 and average total household income. 28 Detailed information on all GWAS included in our study is shown in Table S2.…”
Section: Data Sources For Mediatorsmentioning
confidence: 99%
“…33 The most lateral part of the condyle is depicted as a 2-dimensional image in traditional radiography, such as panoramic radiography. 34 MRI is a technique used to evaluate the TMJ's soft tissue, altered disk position, and effusion 35 and had reduced spatial resolution and thicker slices when used clinically. 36 Hence, it was considered to have lower reliability for detecting TMJ osteoarthritis.…”
Section: R E Su Ltsmentioning
confidence: 99%